THE EFFECT OF METFORMIN TREATMENT ON AUTOPHAGIC FLUX IN BREAST CANCER - Kazbek, Ingkar (Nazarbayev University Graduate School of Medicine, 2024)
Autophagy is a lysosome-mediated intracellular catabolic process that is involved in many physiological and pathological conditions, playing an essential role in preserving cellular homeostasis. Consequently, several studies have indicated dysregulation of autophagy in pathological diseases such as cancer and neurodegenerative disorders. Among various cancer types, breast cancer remains the most common in the world. The increased demand for breast cancer treatment requires advanced therapies and new approaches. Metformin, a commonly prescribed drug for type 2 diabetes, has recently attracted attention as a possible pharmacological autophagy modulator with an anticancer activity. Therefore, the goal of this thesis is to clarify the intricate connection between autophagy and the antidiabetic medication metformin by examining its impact on autophagic flux in breast cancer cell lines.
Keywords: Type of access: Restricted